PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPAS KELAS IV SD NEGERI 158501 SIBULUAN - Sianturi, Yulinda; Safitri , Reviva; Faizal, Jefri; Anggraini, Nia Devi (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Bahasa Institut Pendidikan Tapanuli Selatan, 2025)
This research aims to determine the effect of using the outdoor study method on learning outcomes in science and science learning on norms and customs in my area, class IV at SD Negeri 158501 Sibuluan. The method used is quantitative experimental research using a one group pretest and posttest design. The subjects in this research were 20 students in class IV B of SD Negeri 158501 Sibuluan. The data collection technique uses a test in the form of 10-item multiple choice questions, 5 questions and 5 questions essay. Data analysis techniques use SPSS Version 29 which includes Normality Test, Homogeneity Test, Hypothesis Test. Using the outdoor study method shows that there are significant differences in student learning outcomes before and after being given treatment. Judging from the pretest average, it is 46, while the posttest average value is 75. With the results of the t-test, a significant value (2-tailed) of 0.05 or 0.000 <0.05 is obtained so that Ho is rejected and Ha is accepted. Thus it can be concluded that there is an influence of the use of the method outdoor study on the learning outcomes of students in science and science subjects in class IV of SD Negeri 158501 Sibuluan.